Development Of Interactive E-Modules for Engineering Aspect Workshop Lessons Household Electrical Installation Material - Achmad Zainuri; Iskandar Wiryokusumo; Ibut Priono Leksono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The existence of teaching materials is important in supporting an effective learning process. For this reason, this study aims to develop an interactive E-Module for engineering subjects in the engineering aspects of household electrical installations. Specifically, this study aims to identify the validity of the developed E-Model and determine student responses to the E-Module. This study follows an interactive multimedia development model with stages that include analysis, design, development, evaluation, and implementation. Research data were collected using observation sheets and questionnaires. The results of this study indicate that the developed E-Module is proven valid from the validity test results from design experts, media experts, and materials experts. The students' responses at the trial stage of the limited test, small group, and large group also showed that the developed E-Module received positive responses from students regarding material content, convenience, and message clarity. The results of this study are described in this article using the latest theory and empirical data related to the development and use of E-Modules in learning.